From wall-paintings to electronic technologies: the search for an ideal hybrid space - Braga, Gisele Pinna (PORTO ARTE: Revista de Artes Visuais, 2016)
Man have long used elements of his own architectural works, such as walls, floors and roofs, to devise figurative representations, displaying a different reality from the one before in that very space. Some of them, due to its characteristics, seem to have a virtual (represented) space, spatially integrated with the real (physical) space. We understand the hybrid space as the composition of real and virtual spaces, as if they were one. This article analyzes the representations of many historical periods to analyze the approach of the relationship between real and virtual spaces. He has studied wall-paintings and electronic technologies, showing that elements were gradually incorporated in these representations in order to achieve better results at proposing the hybrid space. He has also considered the ways that telecommunication technologies can contribute to the enabling of an old dream of a hybrid space.